Intoxicação espontânea e experimental por Brachiaria radicans (tanner-grass) em bovinos - Gava, Aldo (2010)
Brachiaria radicans is a grass that grows well on humid soils. In Santa Catarina, it is found mainly in the valleys of the Tubarão and Itajaí rivers. When eaten by cattle in large amounts induces hemolytic anemia, hemoglobinuria, diarrhea and even death. The objective of this study was to evaluate epidemiologic, clinical and pathological data of the intoxication caused by B. radicans in cattle. The plant was administered to 12 cattle in doses of 50-100% of the diet. The animals that received 100% of B. radicans, grown on peaty soils, showed hemoglobinuria, diarrhea and dark red mucous membranes; they recovered when ingestion of the grass was discontinued. Blood and urine tests revealed anemia, hemoglobinuria and proteinuria. Histopathology of organs collected from cattle that died from spontaneous poisoning revealed hepatic centrolobular and paracentralr coagulative necrosis and hemoglobinuric nephrosis. B. radicans proved toxic for cattle only when it grows on fertile soils and is ingested as 100% of the diet.